Fully Coupled Electrothermal Simulation of Large RRAM Arrays in the “Thermal-House” - Da-Wei Wang; Wenchao Chen; Wen-Sheng Zhao; Guo-Dong Zhu; Kai Kang; Pingqi Gao; Jose E. Schutt-Aine; Wen-Yan Yin (IEEE Access)
Thermal crosstalk in a highly integrated RRAM array due to the self-heating effect is one of the most critical issues affecting device reliability. In this paper, two types of “thermal-house” structures are proposed to optimize the thermal management of the RRAM array. An in-house developed parallel simulator is employed to study the performance of the proposed thermal house structures in terms of resistance ratio and crosstalk temperature. It is demonstrated that the proposed thermal house structures can help to reduce thermal crosstalk in high-density RRAM arrays. Some suggestions are also provided for further improving the thermal management capability of the thermal houses as well.